Lowenstein-Jensen Selective Medium for Reducing Contamination in Mycobacterium tuberculosis Culture - Kassaza, Kennedy; Orikiriza, Patrick; Llosa, Augusto; Bazira, Joel; Nyehangane, Dan; Page, Anne-Laure; Boum, Yap (My University, 2014)
We compared Mycobacterium tuberculosis sputum culture recovery and contamination rates between Lowenstein-Jensen medium (LJ) containing the following decontaminants and LJ alone: (i) PANTA (n = 299), (ii) Selectatab-MB (n = 299), and (iii) penicillin G (n = 234). The contamination rate for LJ alone was approximately 31%, versus 5.0% for PANTA-containing, 2% for Selectatab-containing, and 9% for penicillin-containing media (P < 0.001). M. tuberculosis isolation rates were 9.8%, 17%, 18%, and 12% for standard LJ, PANTA, Selectatab, and penicillin cultures, respectively.